Educational video in pre-transplant phase of hematopoietic stem cells - Ana Lúcia Colombo Ikeda; Fernanda Bion Jacques da Cruz; Luciana Martins da Rosa; Jane Cristina Anders; Vera Radünz; Vivian Costa Fermo (Universidade Federal de Santa Maria, 2016)
Aim: to evaluate the quality of educational video presented in the pretransplant stage of hematopoietic stem cell from the perception of transplanted patients. Method: evaluative research, approved by the Ethics Committee, conducted with 31 transplanted patients, from March to August2014, inan oncological institution of Santa Catarina/Brazil. A data collection questionnaire that investigated social data of participants and that collected evaluations about the educational video produced and implemented was applied. The findings were submitted to descriptive statistics, in Excel® Program/Microsoft, version 2007. Results: Most of the patients (90.3%) considered the content of presentation adequate ; 58.1% did not indicate any exclusion; 80.6% considered the video time adequate. The main suggestion to improve the educational videos was to include post-transplant reactions. Conclusion: The transplanted patients evaluated that the video has contributed to the learning and the reduction of anxiety.